2018
DOI: 10.1002/jcb.27388
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of LINC00319 indicates a poor prognosis and promotes cell proliferation and invasion in cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma (CSCC), an epidermal keratinocyte-derived skin tumor, is one of the most leading causes of cancer-associated morbidity and mortality worldwide. Long noncoding RNAs have emerged as key regulators of tumor development and progression. Recent studies have identified LINC00319, a long intergenic noncoding RNA, as an oncogene in lung cancer. However, the biological role of LINC00319 in CSCC remains largely unknown. The current study aimed to explore the role of LINC00319 in CSCC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Here, we have identified a novel lncRNA LINC00319 as a key regulator of miR-3127, and showed that LINC00319 can downregulate the expression of miR-3127 in BCA cells by functioning as a miRNA sponge. LINC00319 was highly expressed in many human tumors and associated with poorer survival of patients (Zhou et al, 2017;Li et al, 2018;Zhang et al, 2018Zhang et al, , 2019Song and Yin, 2019). LINC00319 was shown to promote the proliferative, migratory and invasive capabilities of tumor cells by stabilizing SIRT6 (Zhang et al, 2019) or by interacting with miR-1207 (Song and Yin, 2019), miR-450 (Zhang et al, 2018) and miR-32 (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have identified a novel lncRNA LINC00319 as a key regulator of miR-3127, and showed that LINC00319 can downregulate the expression of miR-3127 in BCA cells by functioning as a miRNA sponge. LINC00319 was highly expressed in many human tumors and associated with poorer survival of patients (Zhou et al, 2017;Li et al, 2018;Zhang et al, 2018Zhang et al, , 2019Song and Yin, 2019). LINC00319 was shown to promote the proliferative, migratory and invasive capabilities of tumor cells by stabilizing SIRT6 (Zhang et al, 2019) or by interacting with miR-1207 (Song and Yin, 2019), miR-450 (Zhang et al, 2018) and miR-32 (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The present study using lncRNA sequencing identified LINC00319 to be significantly upregulated in rCCL18treated OSCC cells. LINC00319 is located in the intergenic region of chromosome 21 and acts as an oncogene in various tumors including ovarian cancer, cutaneous squamous cell carcinoma, glioma, and lung cancer [27][28][29][30] . Previously, the upregulation of LINC00319 was found to be associated with a poor prognosis of cutaneous squamous cell carcinoma patients 28 .…”
Section: Discussionmentioning
confidence: 99%
“…LINC00319 is located in the intergenic region of chromosome 21 and acts as an oncogene in various tumors including ovarian cancer, cutaneous squamous cell carcinoma, glioma, and lung cancer [27][28][29][30] . Previously, the upregulation of LINC00319 was found to be associated with a poor prognosis of cutaneous squamous cell carcinoma patients 28 . In addition, LINC00319 was also found to accelerate tumor growth and metastasis in glioma and lung cancer 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…LINC00319 is a recently identified lncRNA with elevated expression in cSCC shown to correlate with larger tumor size and lymphovascular invasion of cSCC [130]. LINC00319 promotes cSCC cell migration and invasion, and upregulates expression of MMP-2, MMP-9, and markers for epithelial-mesenchymal transition, E-cadherin, and vimentin [130].…”
Section: Precsit and Linc00319 Regulate Invasion Of Csccmentioning
confidence: 99%